Hubungan Antara Keterbukaan Diri Dengan Komunikasi Interpersonal Pada Siswa SMA Hosana Medan - Tampubolon, Ayu Friska; Munir, Abdul (Jouska: Jurnal Ilmiah Psikologi, 2025)
The research was aiming to find out the correlation among self-disclosure with interpersonal communication on students at sma hosana medan. The type of the research was using quantitative correlation. The number of population in the research was involving all of the students in grade X and XI at sma hosana medan. The number of sample in the research was 87 of students, who were taken by using total sample technique. The research data was collected by using likert scale with consist of self- disclosure scale and interpersonal communication scale. Analyzed by using product moment correlation analysis technique. Based on the results of the data analysis was represent the existence of positive correlation among self-disclosure with interpersonal communication, where the coefficient value rxy=0.780 with significance p=0.0000.05. Based on the results calculation hypothetical empirical avarage value on students at sma hosana medan, that they have self-disclosure value in medium category by looking the value of SD =16.960. Known hypothetical mean = 127.5 and empirical mean 142,55 in medium categorized. Where as the interpersonal communication on students sma hosana medan in the high category on value SD= 18,857, mean hypothetical = 140 and empirical mean = 167,80. Futhermore, self-disclosure known having contribution with interpersonal communication in the amount of 60,9℅. In this instance there was 39,1℅ of contribution from other factors that were not disclosed in this research. According to the research above found the hypothetical received when self-disclosure was higher then the interpersonal communication was higer as well on students at sma hosana medan.